Genetic Algorithm Integrated Fuzzy AHP-VIKOR Approach for the Investigation of W-Cut Insert Heat Exchanger for Cooling of Dielectric Fluid Used in Ultra-High Voltage Transformer - N. Vasantha Gowri; J. Samson Isaac; T. Muralikrishna; G. Suresh Babu; Melvin Victor Depoures; S. Sekar; P. Sasirekha; M. Ramesh; S. Prabhakar (Advances in Materials Science and Engineering)
This study proposes a novel W-cut twisted tape to evaluate and enhance the effectiveness of novel grooved tube heat exchanger. The experimental investigations are carried out with W-cut inserts, which possess two main control factors, namely, twist tape ratio (y = 3.5 to 6.5) and width tape ratio (WR = 0.43 to 0.6). The investigation results prove that in all cases the energy transmission and friction factor of W-cut insert along with the first law and second law efficiency are considerably higher than the conventional tube arrangement. The empirical model equations for friction factor, performance enhancement ratio, Nusselt number, and rational efficiency are developed, and they show good affinity with experimental data. Since the abovementioned factors have conflicting terms, it is essential to select the proper operating configuration of the heat exchanger in order to increase the thermal energy transfer rate with reduced consumption of pumping energy. The multi-objective genetic algorithm (GA) tool is used to identify the optimum operating conditions. Further, the hybrid multi-criteria decision-making model, FAHP-VIKOR, is applied to select the perfect model from the set of non-dominated solution. The ranking of alternatives is as follows: A4 > A11 > A2 > A9 > A21 > A17 > A1 > A24 > A11 > A23 > A7 > A18 > A13 > A10 > A20 > A5 > A19 > A14 > A16 > A22 > A25 > A6 > A15 > A3 > A8. The optimized configuration of W-cut insert is compared with the former inserts, and the optimal configuration exhibits supreme performance than other inserts.